Effects of Food Restriction on Rearing Performance and Welfare of a Slow-Growing Chicken Breed: a Behavioural Approach - Lariviere, J-M.; Vandenheede, M.; Leroy, P. (International Journal of Poultry Science, 2009)
The purpose of this experiment was to investigate production and welfare implications of food restriction during the rearing period of a slow-growing chicken. Ninety-four as-hatched day-old Ardennaise chicks were raised up to two weeks of age and were then allocated to two treatment groups: Ad libitum Feeding (AL) and a Feed Restriction Regime (FR). Body weight, food usage and viability were recorded on a weekly basis from 1-12 weeks of age. Activity and oral behaviours were measured at 8, 9, 10, 11 and 12 weeks of age. Number of birds involved in each of twelve mutually exclusive behavioural categories was recorded. Mean proportion of time spent for each activity was calculated. Significance of effects of treatment, age, time of day and their interactions were measured. At 12 weeks of age, mean body weight was 1117 g (± 189.3 g) (AL) and 1054 g (±187.8 g) (FR). Food usage was 4.16 kg (AL) and 3.43 kg (FR) per bird. Feeding treatment had strong effects on preening (p